My Drugs Your Drugs, Indonesia - ., Nurhaedah; Tondok, Santalia Banne; ., Juherah; Arif, M.Ikbal; Aji, Sulistyani Prabu; Izza, Nurril Cholifatul; ., Aminuddin; Pudyastuti, Rita Rena; Zulkarnaen, Iskandar; Wijayanti, Lumastari Ajeng; Pannyiwi, Rahmat (International Journal of Membrane Science and Technology, 2023)
Social Phenomena of Narcotics Circulation, especially Sidenreng Rappang Regency, has not shown maximum results, and even seems to be increasingly rampant to the remote villages. Sidenreng Rappang Regency, South Sulawesi Province, is known as the Lumbung Beras area, recently this positive stigma has shifted that Sidenreng Rappang Regency is now better known as the Narcotics Granary which is one of the drug trafficking centers in South Sulawesi. The results of the study obtained data, in 2015 with the number of 82 cases with 109 suspects, 2016 with 111 cases with 149 suspects, and 2017 with 140 cases with 197 suspects, and 2018 with 59 cases with the number of suspects 99 (Results of direct interviews with Sidrap Police Narcotics Officers and administrative staff, 31 July 2018). 1.Take strict action in accordance with the applicable law towards producers, distributors and users and carry out effective and educative coordination steps with related parties and the community. 2. Strive to increase the budget to rehabilitate victims of narcotics, psychotropic and other addictive substances.